A Scoping Review of the Application of BREAST-Q in Surgical Research - Nikita Arora; Ruchit Patel; Gursharan Sohi; Shaila Merchant; Glykeria Martou (JPRAS Open, 2023)
SUMMARY: Background: Collection of patient-reported outcome (PRO) data can facilitate cost-effective, evidence-based, and patient-centered care. The BREAST-Q has become the gold standard tool to measure PRO data in breast surgery. The last review of its application indicated that it was underutilized. Considering the evolution in breast surgery, the purpose of this study was to perform a scoping review of BREAST-Q application since 2015 and identify emerging trends and potential persistent gaps to guide patient-centered practice and future research in breast surgery. Methods: We performed an electronic literature review to identify publications published in English that used the BREAST-Q to assess patient outcomes. We excluded validation studies, review papers, conference abstracts, discussions, comments, and/or responses to previously published papers. Results: We identified 270 studies that met our inclusion criteria. Specific data was extracted to examine the evolution of the BREAST-Q application and examine clinical trends and research gaps. Discussion: Despite a significant increase in BREAST-Q studies, gaps in the understanding of the patient experience remain. The BREAST-Q is uniquely designed to measure quality of life and satisfaction with outcome and care. The prospective collection of center-specific data for every type of breast surgery will generate important information for the provision of patient-centered and evidence-based care.